2020
DOI: 10.1080/23311932.2020.1807225
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some pretreatments before drying on microbial load and sensory acceptability of dried mango slices during storage periods

Abstract: The present study was conducted to assess the effect of some pretreatments, and drying methods on the microbial loads, and sensory acceptability of dried mango slices during storage periods. Four pretreatments (lemon juice, salt solution dips, hot water blanching, and control) and four drying methods (solar, tray, freeze, and fluidized bed drying) were considered and arranged in factorial experimental design. The microbial loads and sensorial acceptance of dried mango slices during storage times were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Both solar and freeze-drying techniques reduced the total aerobic bacterial count significantly if compared to fresh O. syriacum. Our findings were in agreement with previous studies [31][32][33]. This can be attribute to the fact that removal of moisture makes disturbance and destruction for cell wall as well as for DNA [34].…”
Section: Microbiological Analysis Of Origanum Syriacumsupporting
confidence: 93%
See 1 more Smart Citation
“…Both solar and freeze-drying techniques reduced the total aerobic bacterial count significantly if compared to fresh O. syriacum. Our findings were in agreement with previous studies [31][32][33]. This can be attribute to the fact that removal of moisture makes disturbance and destruction for cell wall as well as for DNA [34].…”
Section: Microbiological Analysis Of Origanum Syriacumsupporting
confidence: 93%
“…It was found that sun-dried ginger had higher content of total bacteria and this was attributed due to contaminants from the surrounded environment [35]. Dereje and Abera [33] found that solar dried mango exhibited higher content fungal count than freeze dried mango. Malmsten et al [32] revealed that freeze-drying was more effective in lowering yeast and mold count than air-drying.…”
Section: Microbiological Analysis Of Origanum Syriacummentioning
confidence: 99%
“…Ripened mangoes are perishable and fresh mangoes are very sensitive to microbial deterioration because of their high-water content. These lead to their short shelf life, and it is a considerable economical and factual issue ( Dereje et al, 2020 , Sehrawat et al, 2018 ). Therefore, deep processing and preservation methods have been extensively pursued to expand the storage and consumption of fresh mangoes.…”
Section: Introductionmentioning
confidence: 99%
“…Drying is one of the most typical and economic processing methods applied to reduce post-harvest product loss and increase the shelf life of products. This inhibits bacterial growth and hinders putrefaction reactions mainly attributed to the reduced moisture content ( Dereje et al, 2020 , Kumar et al, 2014 , Macedo et al, 2020 ). Traditional drying methods include drying in the sun or shade, which are time-consuming.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation